JOB SATISFACTION OF MEDICAL STAFF AT NATIONAL OTORHINORARYNOLOGY HOSPITAL OF VIETNAM, 2019 (Vietnam Journal of Community Medicine, 2021)
Objective: Evaluation of job satisfaction of medical staff at National Otorhinorarynology Hospital of Vietnam, 2019.Methods: Design a cross-sectional descriptive study, interview 306 health workers according to a set of prepared questionnaires built on the two-factor theory of Ferederick Herzberg.Results: The overall satisfaction rate of medical staff is high, reaching 95.4%. health workers are most satisfied with their relationship with colleagues 93.5%, followed by learning and developmentopportunities 91.8%, income and policies, both are 88.9%, on benefits 88.6%, on supervisor supervision 88.2% and finally on working conditions 82.7%. Logistic regression analysis showedthat the overall satisfaction rate in the married group was lower than the single group (OR=0.75; 95%CI: 0.42-0.99; p
Keywords: Satisfaction of medical staff; National Otorhinorarynology Hospital